Analisis Pengaruh Faktor Nilai Hidup, Kemandirian, Dan Dukungan Keluarga Terhadap Perilaku Sehat Lansia Di Kelurahan Medono Kota Pekalongan - Pratikwo, Suryo; Pietojo, Harbandinah; Widjanarko, Bagoes (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background: The number of elderly people has been increasing from 6.8% in 2002 to 7.15% in 2003 in Medono village Pekalongan. Nearly 98% of them are still living with their own family. Therefore, the role of family members in maintaining and motivating positive value of life as well as improving positive health behaviour of their elderly has been increasingly important. This study examines the factors of the elderly value of life, their independency and their family supports which influence their positive health behaviour in Medono village.Method : A survey method using a structured-scheduled questionnaire and a face to face interview which involved 60 sample has been employed in this study. Likewise, an observation method using a check list technique has also been used to observe the independency and personal hygine behaviour factors of the respondents. The data was analyzed using univariate, bivariate and multivariate (particularly logistic regression) analyses.Results : The study found that there were significant correlations between age, education level, value of life and family support factors of the elderly and their positive health behaviour since Chi-square test shows p<0.05. However, there was no correlation between gender and the elderly behaviour. Likewise, multivariate analysis also shows that positive value of life is a dominant factor which predict the elderly positive health behaviour.Keywords: Elderly, Health Behaviour, Value of Life, Independency, Family Supports